Expression and prognostic significance of the m6A RNA methylation regulator HNRNPC in HNSCC - Zhang, Yulin; Wang, Yixu; Peng, Jilin; Zhao, Kun; Li, Ling; Zhang, Yuan; Zhai, Ziyu; Yuan, Sijie; Li, Shichao; Ye, Fanglei; Wang, Le (Frontiers in Oncology, 2025)
BackgroundN6-methyladenosine (m6A) RNA modification is crucial for tumor development and progression; however, which m6A regulators play a pivotal role in head and neck squamous cell carcinoma (HNSCC) remains ambiguous.MethodsUtilizing the Cancer Genome Atlas (TCGA) database, the expression levels of m6A regulators in HNSCC were examined, which led to the identification of heterogeneous nuclear ribonucleoprotein C (HNRNPC) as a key gene. Further experiments were performed in patient samples, stable cell lines, and a murine xenograft tumor model.ResultsA reliable survival risk model of m6A was constructed based on the TCGA database. Gene Expression Omnibus (GEO), normal and tumor tissue microarrays (TMA), and tumor tissue samples from patients with HNSCC were observed that a high level of HNRNPC expression was closely linked to a poor prognosis among patients. Knockdown of HNRNPC in the HNSCC cell lines HSC-3 and CAL-27 resulted in a significant decrease in proliferation, invasion, and malignant transformation abilities. RNA sequencing (RNA-seq) and methylated RNA immunoprecipitation and sequencing (MeRIP-seq) data revealed that HNRNPC is involved in cell differentiation, cell migration and apoptosis. The mouse xenograft model elucidated that HNRNPC can promote tumorigenesis and progression of HNSCC.ConclusionsHNRNPC can serve as a valuable predictor of tumor progression and prognosis in patients with HNSCC.